Optimization of Zakat Management Program in Supporting Sustainable Development Goals by Lembaga Manajemen Infaq - Syafiatul Makrifah Maysarah; Meilia Sukmawati; Ahmad Baka Putra Karozma; Hari Nopriansyah (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2026)
This research is motivated by the limited public access to clean water in several areas of Ponorogo, Indonesia, as well as the lack of sustainable zakat-based empowerment programs. Specifically, it addresses sixth goals on access to clean water and sanitation. The study aims to analyze how the distribution of zakat, particularly through clean water programs, can support the achievement of the SDGs. This study employs a descriptive analysis and utilizes primary data from interviews with employees at LMI Ponorogo. The results indicate that productive distribution, especially through the construction of boreholes and infiltration wells - has a significant impact on improving community access to clean water, while also providing added value in the areas of education and the environment. The findings of this study suggest that zakat is not merely an instrument of consumptive philanthropy but can also be optimized as a mechanism for sustainable development with systemic impact.